Awareness and Willingness to Pay for Community Based Health Insurance in Ikorodu Local Government Area (Western Journal of Medical and Biomedical Sciences, 2024)
Community Based Health Insurance schemes (CBHIS) help to provide financial risk protection and improve the quality of health care. An effective and reliable willingness to pay information for a target population would facilitate scheme design and implementation. The study aimed to assess the awareness and willingness to pay as well as factors influencing the willingness to pay for the CBHIS among households in Ikorodu, a semi-urban community in Lagos state, Nigeria. It was a descriptive cross-sectional study carried out among 422 household heads in Ikorodu Local Government Area using multistage sampling method. Information was obtained with a structured interviewer administered questionnaire. Data analysis was by using Epi-info version 7.0 and results presented as frequency tables and cross-tabulations. The mean age of the 422 respondents was 40.6 + 10.4 years. Most were males (61.6%), married (83.4%) and 0.7% without formal education. While awareness about CBHI was low among the respondents with only 10.7% being aware of the existence of CBHI, 96.5% believed such a scheme would be beneficial. Majority (98.8%) of the respondents were willing to enroll and pay into the proposed expanded CBHI scheme. Those willing to pay the opening premium of N400 were 88.2%. The mean amount respondents were willing to pay was N538.8 + 227.0 and the allowable range for fixing premium was between N100 and N2000. A bi-variate analysis showed that the factors affecting willingness to pay were educational level, occupation, income and past health expenditure of household heads. The study showed some differentials in the level of premium payment acceptable to different socio-economic groups and it may be necessary to factor this into the design of CBHI scheme for example by providing different packages commensurate with level of premium paid. Though this study showed low level of awareness of CBHI among respondents, it also showed a very high level of willingness to participate in CBHI once the respondents had adequate information.
Keywords: Awareness; Community based health Insurance; PPremium; Willingness to pay